Carbon balance for biosolids use in commercial Douglas Fir plantations in the Pacific Northwest. (1st October 2021) - Leonard, Emma; Bodas, Jyoti; Brown, Sally; Axt, Ben
Abstract: Municipal biosolids are commonly used to fertilize Douglas fir ( Pseudotsuga menziesii ) plantations in the Pacific Northwest. An intensive soil sampling was conducted to quantify the effects of long-term biosolids application on soil carbon, nitrogen and bulk density for forest soils. This information was used to calculate a carbon balance for biosolids use in commercial tree plantations. Paired control and treated sites on two soil series (Klaus and Tokul) were included with samples collected to a 30 cm depth. A significant decrease in bulk density for two depths, but no changes in total C or N were observed in the Klaus soil. In the Tokul soil, biosolids fertilization increased C storage (total C * bulk density) for three of the four measured depths, resulting in an increase in total C from 112.8 Mg C ha −1 to 172 Mg C ha −1 for the 0–30 cm depth. A comparable increase in N was observed, with significant increases in N storage for all measured depths. The C balance considered fuel use associated with transport and application as costs. The fertilizer (N and P) content of the biosolids and changes in soil C were considered as credits. The balance showed net sequestration for both soil series. Carbon benefits for the Klaus soil totaled −0.2 Mg CO2 per Mg biosolids. Benefits in the Tokul soil totaled −5.15 Mg CO2 per Mg biosolids. Based on diameter at breast height (DBH) biosolids use also resulted in increased tree growth for both soil series. However, differences in stand age and stocking rate complicated interpretation of these results. Graphical abstract: Image 1 Highlights: We sampled soils and measured tree growth to document changes as a result of long-term biosolids application to commercial tree plantations in the Pacific Northwest Significant carbon and nitrogen storage were seen on the lower organic matter site. No changes were seen on the higher organic matter site. A carbon balance was carried and showed significant carbon storage at the lower organic matter site with a small credit at the higher organic matter site.